Formulation Cream of Extract Moringa oleifera Leave as Antiaging - Nining Sugihartini; Evi Nuryanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Moringa oleifera leaf as natural material has the activity to protect skin because it contains antioxidants. Therefore, the development of dosage forms in the form of a antiaging cream is required to be used by the human. Purpose: To determine the concentration of extract moringa oleifera leaf which will provide the ability as antiaging. Methods: Extract of moringa oleifera leaf was obtained by maceration methods by ethanol 70% as solvent. Then extract was formulated in dosage forms an antiaging cream with concentration of variations are formula I (0%), formula II (3%), formula III (6%) and the formula IV (9%). After that cream was evaluated with parameters moisture, evenness, pore, spot and wringkle on human probandus whom have used the cream for 14 days. Results: Increasing the concentration of Moringa oleifera leaf extract led to a decreasing evenness (p<0.05) which efective on concentration 3%. Conclusion: The concentration of Moringa oleifera  leaf extract that can be used as antiaging which decreasing evenness was 3%.